MENCERMATI PERBEDAAN MODEL ASSURE DAN ADDIE DALAM METODOLOGI PENGEMBANGAN PEMBELAJARAN PAI - Haq, Vick Ainun (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Learning Development Methodology in PAI (Islamic Religious Education) subjects is something that cannot be ruled out, especially on the theme of Avoiding Free Association, Al-Qur'an Hadith lessons. Meanwhile, prior to implementing KBM (Teaching and Learning Activities) requires careful readiness, to support this learning the ASSURE and ADDIE models are the right things to facilitate the development of teaching and learning in the classroom. This article aims to describe the steps for implementing the ASSURE and ADDIE models in learning the material on Avoiding Free Association, while the method used in this research is to use a qualitative approach, with the type of library research. Furthermore, the results of this study indicate that the application of the ASSURE and ADDIE models in the subject of the Qur'an Hadith with the theme of Avoiding Free Association has a significant difference, where the ASSURE model prioritizes the role of educators in interaction with students, or focuses more on classroom interactions. While the ADDIE model shows how educators play a role in shaping/influencing students according to the planned design.